Early Degeneration of Both Dopaminergic and Serotonergic Axons - A Common Mechanism in Parkinson's Disease - Grosch, Janina; Winkler, Jürgen; Kohl, Zacharias (Frontiers in Cellular Neuroscience, 2016)
Motor symptoms in Parkinson's disease (PD) are tightly linked to the degeneration of substantia nigra dopaminergic neurons and their projections into the striatum. Moreover, a broad range of non-motor symptoms like anxiety and depression frequently occur in PD, most likely related to the loss of serotonergic neurons and their projections into corresponding target regions. Strikingly, nigral dopaminergic neurons and raphe serotonergic neurons are severely affected in PD showing characteristic hallmarks of PD neuropathology, in particular alpha-synuclein containing Lewy bodies and Lewy neurites. So far, the initial events underlying neurodegenerative processes in PD are not well understood. Several observations, however, indicate that neurites and synapses of diseased neurons may be the first subcellular compartments compromised by alpha-synuclein associated pathology. In particular axonal pathology and deficits in axonal transport may be leading to the onset of synucleinopathies such as PD. This review will highlight current findings derived from imaging and neuropathological studies in PD patients, as well as cellular and animal PD models, which define the initial underlying structural and molecular events within dopaminergic and serotonergic circuits leading to the 'dying back' degeneration of axonal projections in PD.
EVALuna2:33511

Intracellular alpha-synuclein affects early maturation of primary oligodendrocyte progenitor cells - Ettle, Benjamin; Reiprich, Simone; Deußer, Janina; Schlachetzki, Johannes; Xiang, Wei; Prots, Iryna; Masliah, Eliezer; Winner, Beate; Wegner, Michael; Winkler, Jürgen (Molecular and Cellular Neuroscience, 2014)
Myelin loss is a widespread neuropathological hallmark of the atypical parkinsonian disorder multiple system atrophy (MSA). On a cellular level, MSA is characterized by alpha-synuclein (aSyn)-positive glial cytoplasmic inclusions (GCIs) within mature oligodendrocytes leading to demyelination as well as axonal and neuronal loss. Oligodendrocyte progenitor cells (OPCs) represent a proliferative cell population distributed throughout the adult mammalian central nervous system. During remyelination, OPCs are recruited to sites of demyelination, differentiate, and finally replace dysfunctional mature oligodendrocytes. However, comprehensive studies investigating OPCs and remyelination processes in MSA are lacking. In the present study, we therefore investigate the effect of human aSyn (h-aSyn) on early primary rat OPC maturation. Upon lentiviral transduction, h-aSyn expressing OPCs exhibit fewer and shorter primary processes at the initiation of differentiation. Until day 4 of a 6day differentiation paradigm, h-aSyn expressing OPCs further show a severely delayed maturation evidenced by reduced myelin gene expression and increased levels of the progenitor marker platelet derived growth factor receptor-alpha (PDGFR?). Matching these results, OPCs that take up extracellular recombinant h-aSyn exhibit a similar delayed differentiation. In both experimental setups however, myelin gene expression is restored at day 6 of differentiation paralleled by decreased intracellular h-aSyn levels indicating a reverse correlation of h-aSyn and the differentiation potential of OPCs. Taken together, these findings suggest a tight link between the intracellular level of h-aSyn and maturation capacity of primary OPCs.
EVALuna2:4696

Layer-specific axonal degeneration of serotonergic fibers in the prefrontal cortex of aged A53T α-synuclein–expressing mice - Wihan, Jeanette; Grosch, Janina; Kalinichenko, Liubov; Müller, Christian P.; Winkler, Jürgen; Kohl, Zacharias (Neurobiology of Aging, 2019)
Axonal pathology precedes dopaminergic cell loss in Parkinson's disease (PD), indicating a dying back axonopathy of nigrostriatal projections. Although most attention focused on the dopaminergic system, increasing evidence implies a compromised serotonergic system in PD as well. By combining immunohistological and biochemical approaches, a profound layer-specific reduction of the serotonergic input to the prefrontal cortex (PFC)layers II and V/VI in aged mutant A53T α-synuclein–expressing mice (A53T mice)was detected. In addition, the altered fiber network was characterized by swollen axons and enlarged axonal varicosities within all PFC layers, but most pronounced in PFC layer I. Although prefrontal serotonin levels and synaptic protein expression were preserved, aged A53T mice showed increased levels of kinesin family member 1a and vesicular monoamine transporter 2. Together with increased tryptophan hydroxylase 2 mRNA levels in the raphe nuclei and an elevated serotonin receptor 1b expression in the PFC, these findings point to compensatory mechanisms within the serotonergic system to overcome the reduced neuritic input to the PFC in this transgenic animal model for PD.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Alpha-synuclein; Parkinson's disease; Prefrontal cortex; Serotonin; Serotonin transporter

Need for high-resolution Genetic Analysis in iPSC: Results and Lessons from the ForIPS Consortium - Popp, Bernt; Krumbiegel, Mandy; Grosch, Janina; Sommer, Annika; Uebe, Steffen; Kohl, Zacharias; Ploetz, Sonja; Farrell, Michaela; Trautmann, Udo; Kraus, Cornelia; Ekici, Arif Bülent; Asadollahi, Reza; et al. (Scientific Reports, 2018)
Genetic integrity of induced pluripotent stem cells (iPSCs) is essential for their validity as disease models and for potential therapeutic use. We describe the comprehensive analysis in the ForIPS consortium: an iPSC collection from donors with neurological diseases and healthy controls. Characterization included pluripotency confirmation, fingerprinting, conventional and molecular karyotyping in all lines. In the majority, somatic copy number variants (CNVs) were identified. A subset with available matched donor DNA was selected for comparative exome sequencing. We identified single nucleotide variants (SNVs) at different allelic frequencies in each clone with high variability in mutational load. Low frequencies of variants in parental fibroblasts highlight the importance of germline samples. Somatic variant number was independent from reprogramming, cell type and passage. Comparison with disease genes and prediction scores suggest biological relevance for some variants. We show that high-throughput sequencing has value beyond SNV detection and the requirement to individually evaluate each clone.
EVALuna2:34839

Role of the receptor Mas in macrophage-mediated inflammation in vivo - Hammer, Anna; Yang, Guang; Friedrich, Juliane; Kovacs, Agnes; Lee, De-Hyung; Grave, Katharina; Joerg, Stefanie; Alenina, Natalia; Grosch, Janina; Winkler, Jürgen; Gold, Ralf; Bader, Michael; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Recently, an alternative renin-angiotensin system pathway has been described, which involves binding of angiotensin-(1-7) to its receptor Mas. The Mas axis may counterbalance angiotensin-II-mediated proinflammatory effects, likely by affecting macrophage function. Here we investigate the role of Mas in murine models of autoimmune neuroinflammation and atherosclerosis, which both involve macrophage-driven pathomechanisms. Mas signaling affected macrophage polarization, migration, and macrophage-mediated T-cell activation. Mas deficiency exacerbated the course of experimental autoimmune encephalomyelitis and increased macrophage infiltration as well as proinflammatory gene expression in the spleen and spinal cord. Furthermore, Mas deficiency promoted atherosclerosis by affecting macrophage infiltration and migration and led to increased oxidative stress as well as impaired endothelial function in ApoE-deficient mice. In summary, we identified the Mas axis as an important factor in macrophage function during inflammation of the central nervous and vascular system in vivo. Modulating the Mas axis may constitute an interesting therapeutic target in multiple sclerosis and/or atherosclerosis.
EVALuna2:22496

Serotonergic dysfunction in the A53T alpha-synuclein mouse model of Parkinson's disease - Deußer, Janina; Schmidt, Stefanie; Ettle, Benjamin; Ploetz, Sonja; Huber, Sabine; Müller, Christiane; Masliah, Eliezer; Winkler, Jürgen; Kohl, Zacharias (Journal of Neurochemistry, 2015)
Parkinson's disease, neuropathologically defined by the aggregation of ?-synuclein, is characterized by neuropsychiatric symptoms such as depression and anxiety preceding the onset of motor symptoms. A loss of serotonergic neurons or their projections into the hippocampus and alterations in serotonin release may be linked to these symptoms. Here, we investigate the effect of human A53T ?-synuclein on serotonergic neurons using 12-months-old transgenic mice. We detected human ?-synuclein in the perikarya of brainstem median and dorsal raphe neurons as well as in serotonergic fibers in the hippocampus. Despite intracellular ?-synuclein accumulation there was no loss of serotonergic neurons in dorsal and median raphe nuclei of A53T ?-synuclein mice. However, serotonin levels were significantly reduced in the brainstem. In addition, serotonergic fiber density in the dorsal dentate gyrus was significantly less dense in transgenic mice. Interestingly, we detected a significantly compromised increase in doublecortin+ neuroblasts after chronic treatment with fluoxetine at the site of reduced serotonergic innervation, the infrapyramidal blade of the dorsal dentate gyrus in A53T ?-synuclein mice. This suggests that ?-synuclein affects serotonergic projections in a spatially distinct pattern within the hippocampus thereby influencing the response to antidepressant treatment.
EVALuna2:23680

Severely impaired hippocampal neurogenesis associates with an early serotonergic deficit in a BAC ?-synuclein transgenic rat model of Parkinson's disease - Kohl, Zacharias; Ben Abdallah, Nada; Vogelgsang, Jonathan; Tischer, Lucas; Deußer, Janina; Amato, Davide; Anderson, Scott; Müller, Christian P.; Riess, Olaf; Masliah, Eliezer; Nuber, Silke; Winkler, Jürgen (Neurobiology of Disease, 2016)
Parkinson's disease (PD) is a multisystem disorder, involving several monoaminergic neurotransmitter systems resulting in a broad range of motor and non-motor symptoms. Pathological hallmarks of PD are the loss of dopaminergic neurons and the accumulation of alpha-synuclein, however also being present in the serotonergic raphe nuclei early in the disease course. The dysfunction of the serotonergic system projecting to the hippocampus may contribute to early non-motor symptoms such as anxiety and depression. The adult hippocampal dentate gyrus (DG), a unique niche of the forebrain continuously generating new neurons, may particularly present enhanced susceptibility towards accumulating alpha-synuclein levels. The underlying molecular mechanisms in the context of neuronal maturation and survival of new-born neurons are yet not well understood. To characterize the effects of overexpression of human full-length alpha-synuclein on hippocampal cellular and synaptic plasticity, we used a recently generated BAC alpha-synuclein transgenic rat model showing important features of PD such as widespread and progressive alpha-synuclein aggregation pathology, dopamine loss and age-dependent motor decline. At the age of four months, thus prior to the occurrence of the motor phenotype, we observed a profoundly impaired dendritogenesis of neuroblasts in the hippocampal DG resulting in severely reduced survival of adult new-born neurons. Diminished neurogenesis concurred with a serotonergic deficit in the hippocampus as defined by reduced levels of serotonin (5-HT) 1B receptor, decreased 5-HT neurotransmitter levels, and a loss of serotonergic nerve terminals innervating the DG/CA3 subfield, while the number of serotonergic neurons in the raphe nuclei remained unchanged. Moreover, alpha-synuclein overexpression reduced proteins involved in vesicle release, in particular synapsin-1 and Rab3 interacting molecule (RIM3), in conjunction with an altered ultrastructural architecture of hippocampal synapses. Importantly, BAC alpha-synuclein rats showed an early anxiety-like phenotype consisting of reduced exploratory behavior and feeding. Taken together, these findings imply that accumulating alpha-synuclein severely affects hippocampal neurogenesis paralleled by impaired 5-HT neurotransmission prior to the onset of aggregation pathology and overt motor deficits in this transgenic rat model of PD.
EVALuna2:23681

Sporadic Parkinson's disease derived neuronal cells show disease-specific mRNA and small RNA signatures with abundant deregulation of piRNAs - Schulze, Markus; Sommer, Annika; Plotz, Sonja; Farrell, Michaela; Winner, Beate; Grosch, Janina; Winkler, Jürgen; Riemenschneider, Markus J. (Acta Neuropathologica Communications, 2018)
Differentiated neurons established via iPSCs from patients that suffer from familial Parkinson's disease (PD) have allowed insights into the mechanisms of neurodegeneration. In the larger cohort of patients with sporadic PD, iPSC based information on disease specific cellular phenotypes is rare. We asked whether differences may be present on genomic and epigenomic levels and performed a comprehensive transcriptomic and epigenomic analysis of fibroblasts, iPSCs and differentiated neuronal cells of sporadic PD-patients and controls. We found that on mRNA level, although fibroblasts and iPSCs are largely indistinguishable, differentiated neuronal cells of sporadic PD patients show significant alterations enriched in pathways known to be involved in disease aetiology, like the CREB-pathway and the pathway regulating PGC1a. Moreover, miRNAs and piRNAs/piRNA-like molecules are largely differentially regulated in cells and post-mortem tissue samples between control-and PD-patients. The most striking differences can be found in piRNAs/piRNA-like molecules, with SINE-and LINE-derived piRNAs highly downregulated in a disease specific manner. We conclude that neuronal cells derived from sporadic PD-patients help to elucidate novel disease mechanisms and provide relevant insight into the epigenetic landscape of sporadic Parkinson's disease as particularly regulated by small RNAs.
EVALuna2:35781

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Marxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Gräf, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2019)
EVALuna2:203042

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Maxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Graef, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding using autologous co-cultures of activated T lymphocytes and iPSC-derived MBNs of sporadic PD patients and controls. After co-culture with T lymphocytes or the addition of IL-17, PD iPSC-derived MBNs underwent increased neuronal death driven by upregulation of IL-17 receptor (IL-17R) and NF kappa B activation. Blockage of IL-17 or IL-17R, or the addition of the FDA-approved anti-IL-17 antibody, secukinumab, rescued the neuronal death. Our findings indicate a critical role for IL-17-producing T lymphocytes in sporadic PD.
EVALuna2:35782

α-Synuclein oligomers induce early axonal dysfunction in human iPSC-based models of synucleinopathies - Prots, Iryna; Grosch, Janina; Brazdis, Razvan-Marius; Simmnacher, Katrin; Veber, Vanesa; Havlicek, Steven; Hannappel, Christian; Krach, Florian; Krumbiegel, Mandy; Schuetz, Oliver; Reis, André; Wrasidlo, Wolfgang; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
α-Synuclein (α-Syn) aggregation, proceeding from oligomers to fibrils, is one central hallmark of neurodegeneration in synucleinopathies. α-Syn oligomers are toxic by triggering neurodegenerative processes in in vitro and in vivo models. However, the precise contribution of α-Syn oligomers to neurite pathology in human neurons and the underlying mechanisms remain unclear. Here, we demonstrate the formation of oligomeric α-Syn intermediates and reduced axonal mitochondrial transport in human neurons derived from induced pluripotent stem cells (iPSC) from a Parkinson's disease patient carrying an α-Syn gene duplication. We further show that increased levels of α-Syn oligomers disrupt axonal integrity in human neurons. We apply an α-Syn oligomerization model by expressing α-Syn oligomer-forming mutants (E46K and E57K) and wild-type α-Syn in human iPSC-derived neurons. Pronounced α-Syn oligomerization led to impaired anterograde axonal transport of mitochondria, which can be restored by the inhibition of α-Syn oligomer formation. Furthermore, α-Syn oligomers were associated with a subcellular relocation of transport-regulating proteins Miro1, KLC1, and Tau as well as reduced ATP levels, underlying axonal transport deficits. Consequently, reduced axonal density and structural synaptic degeneration were observed in human neurons in the presence of high levels of α-Syn oligomers. Together, increased dosage of α-Syn resulting in α-Syn oligomerization causes axonal transport disruption and energy deficits, leading to synapse loss in human neurons. This study identifies α-Syn oligomers as the critical species triggering early axonal dysfunction in synucleinopathies.
EVALuna2:34623
Keywords: alpha-synuclein; oligomers; axonal transport; synucleinopathies; neurodegeneration